Hyperbaric oxygen therapy for radiation enteritis and clinical parameters: a systematic review and meta-analysis - Wang, Yuhan; Yang, Xuhui; Jiang, Minjiao; Tang, Zili; Zhao, Ling (Frontiers in Medicine, 2025)
BackgroundHyperbaric oxygen therapy (HBOT) has been debated regarding its efficacy and safety in treating radiation enteritis (RE), with no standardized clinical protocols established. This study evaluates the clinical evidence on the use of HBOT in the management of RE, focusing on efficacy, safety, treatment parameters, and potential mechanisms.MethodsA comprehensive computer-based search was conducted across nine databases. The study assessed the effects of HBOT on gastrointestinal symptoms, immune function, inflammation, and its role in reducing the incidence of moderate to severe RE. Additionally, clinical application protocols were analyzed.ResultsThis study analyzed data from 22 clinical studies involving 1,318 subjects, including six RCTs incorporated into a meta-analysis. Moderate-quality evidence suggested that HBOT could significantly reduce the incidence of RE [OR = 0.32, 95% CI (0.14, 0.72), P = 0.006], particularly showing a significant advantage in decreasing the incidence of grade 3 or higher RE according to the RTOG/EORTC criteria [OR = 0.37, 95% CI (0.17, 0.82), P = 0.01]. Additionally, HBOT was shown to effectively improve gastrointestinal symptoms [MD = −1.31, 95% CI (−2.48, −0.13), P = 0.03]. Low-quality evidence suggested that HBOT reduced inflammatory markers (IL-6, CRP, TNF-α) and increased immunoglobulin levels (IgA, IgG, IgM). The most commonly reported protocol parameters were 2.0–2.5 ATA, 90–120 min per session, once daily, five times per week, for 30–40 sessions.ConclusionThis study demonstrates that HBOT effectively alleviates gastrointestinal symptoms, promotes mucosal repair, reduces inflammation, and enhances immune function in patients with RE. HBOT significantly decreases the incidence of RE, particularly severe enteritis. Optimized treatment protocols and individualized adjustments are essential for achieving optimal outcomes. Despite the potential benefits of HBOT for RE, caution is still warranted in clinical practice, with optimization of treatment protocols and individualized adjustments to ensure optimal efficacy.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42024618971